Pengaruh Kepemilikan Manajerial, Total Asset Turnover, dan Ukuran Perusahaan Terhadap Struktur Modal - Safira Aura Cahyani; Tresno Eka Jaya; Diah Armeliza (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
Focusing on basic materials firms listed on the Indonesia Stock Exchange from 2022 to 2024, this research explores whether managerial ownership, asset turnover, and firm size affect capital structure decisions. Secondary data from annual reports were analyzed using panel regression on 120 observations drawn from 40 purposively selected companies. The empirical findings indicate that only firm size emerges as a significant determinant, while the other two variables fail to reach statistical significance. Consequently, the evidence points to firm size as the primary driver of capital structure in this sector, overshadowing managerial equity stakes and operational efficiency metrics.